Views of the Baltic German Press on the Traditions: of Other Nationalities in Riga’s Music Life in the 1870s–1880s: The Influence of the Political Context - Jaunslaviete Baiba (Musicology Today)
The history of German presence in the territory of Latvia began in the thirteenth century, when Germans arrived here as crusaders. From that time until the nineteenth century, they played the dominant role in the economic and political life of the region. In the second half of the nineteenth century, however, the situation changed. After the abolition of serfdom (1817–1819), Latvians greatly improved their economic and educational status, and the new Latvian intelligentsia expressed its opposition to German dominance in the region. The Latvian national revival of that period was supported by the Russian authorities with a somewhat selfish interest.